Anthracycline-based combination chemotherapy (Doxorubicin and Dacarbazine) for the desmoid tumor in a neoadjuvant setting. Report of a case - Mahmood S; Divyanshu Dua (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
We report a case of a 41-years-old female with a sporadic abdominal wall desmoid tumor. After a period of 12-months observation, chemotherapy was given with Doxorubicin and Dacarbazine to facilitate minimal surgery. The patient received 4 cycles of chemotherapy. Treatment was well tolerated and resulted in a significant reduction of the tumor size from 48mm to 25mm, 48% reduction. The tumor was surgically resected, and the histopathology from the resected specimen revealed a partial pathological response. At 6 months post-surgery, there is no recurrence or surgical complications.